H. Clay Naill correspondence - Naill, H. Clay (Henry Clay)
ALS (1860 November 30) from Naill to his father, David W. Naill, concerning the secession crisis in Baltimore, Md.
Maryland state legislator and public official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Naill, David W. -- Correspondence; Secession -- Maryland; Baltimore (Md.) -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865.; Maryland -- Politics and government -- 1775-1865.; Legislators -- Maryland; Public officials -- Maryland